Marketing executives’ turnover and firm performance - Vaid, Sash; Ahearne, Michael; Krause, Ryan; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2021)
This research takes a disruption-adaptation perspective to understand influence of marketing executives’ turnover (MET) on firm performance. The authors draw on marketing (and sales) executive exits at U.S. public firms between 2004 and 2016. MET measures presence (or absence) of annual turnover of one or more executives, accounting for changes (due to exits) to marketing organization’s formal representation in the top management. We show that MET hurts firm performance as it disrupts functioning of customer-facing marketing positions that hurts buyer-supplier relationships. Building on Hancock et al.’s (2013) meta-analysis of some 25,000 turnovers, we find that MET’s association with firm performance is worsened in firm-level environments characterized by demotions (indicating disagreements between management and executives), and voluntary peer exits (indicating low motivation and self-efficacy). However, MET’s disruptive influence on firm performance is attenuated in firms with greater degree of executive transience (indicating premium on stability in systems burdened by executive histories of job-hopping behavior), and debt to assets ratio (indicating disciplining mechanism that signals firm’s quality during periods of change such as mergers, takeovers and bankruptcies). Valuation Insight: The importance of marketing executives in adding value to the corporation is illustrated by evaluation of the effect of marketing executives’ turnover on firm performance. Increased turnover of marketing executives is found to significantly decrease firm performance.
56 p. ; Includes bibliographical references (pp. 40-48) ; Last revision: December 1, 2021 ; The authors would like to thank anonymous reviewers for their constructive comments on previous versions of this paper.
Keywords: Marketing executives’ turnover; Firm performance; Disruption; Adaptation; Dynamic panel